Pengendalian Kualitas Produk Plastik Jenis Polypropylene Menggunakan Metode Seven Tools Pada PT.Kusuma Mulia Plasindo Infitex - Ari Zaqi Al Faritsy; Ihsan syaifuddin, Ihsan syaifuddin (Jurnal Ilmiah Teknik Mesin, Elektro dan Komputer, 2023)
ABSTRACT Kusuma Mulia Plasindo Infitex is a company engaged in the manufacturing sector that produces products, one of which is polypropylene plastic. The problems that occurred at PT. Kusuma Mulia Plasindo Infitex is the occurrence of products that do not comply with standards or defective products. Types of defective products include side breaks and folds in the middle with a total of 277 defective products. The purpose of this study was to determine the factors that cause defects in PT. Polypropylene plastic products. Kusuma Mulia Plasindo Infitex . This study uses the seven tools method. The seven tools method uses 7 quality control tools, namely Check Sheets, Control Charts, Cause and Effect Diagrams, Pareto Diagrams, Histograms, Scatter Diagrams and Flowcharts. From the results of research using the seven tools method, it can be seen that the causes of defects in Polypropylene plastic products are caused by 4 aspects, namely machine factors caused by age and machine maintenance, materials that are not according to standards, human factors caused by lack of training and factors of workers' methods that are not according to SOP/standard operating procedures. Keywords: Quality Control, Polypropylene plastic products, Seven Tool.